PENGARUH MODEL PEMBELAJARAN JOYFUL LEARNING TERHADAP HASIL BELAJAR IPAS KELAS IV UPTD SD NEGERI 125549 PEMATANGSIANTAR - Simanjuntak, Melvin; Desi Sijabat; Malika Situmorang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine the effect of using the Joyful Learning model on science learning outcomes of fourth-grade students at UPTD SD Negeri 125549 Pematangsiantar. This study used a quantitative approach. The research design used was an experiment, with a pre-experimental design, and the sample size was 20 students. The instrument used in this study was a multiple-choice test. The results of the hypothesis testing obtained data on the average results of the experimental class in the pretest (48.5) and posttest (84.25). The hypothesis was tested using a t-test, where t-test > t-table (13.900 > 1.729) with a significance level of 0.05. Therefore, it can be concluded that the use of the Joyful Learning model has an effect on the science learning outcomes of fourth-grade students at the UPTD of SD Negeri 125549 Pematangsiantar.